Pharmacogenomics in Pancreatic Adenocarcinoma: New Data and Their Clinical Implications - Strimpakos, Alexios S; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
<!--[if gte mso 9]> Normal 0 false false false EL X-NONE X-NONE <![endif]--> Despite advances and investments in translation research, clinical trials and health service in general, there is no significant impact on the survival of most patients diagnosed with advanced pancreatic adenocarcinoma. It is broadly recognized though that there is a small minority of patients who really benefit from particular treatments for reason usually not well understood. Light to this fact is gradually shed by developments in the field of pharmacogenomics, which plays pivotal role in what we call individualized medicine. In that perspective, it is of most importance to present the significant developments in pharmacogenomics announced in the recent 2013 American Society of Clinical Oncology Annual Meeting. First, the predictive role of hENT1, which codes for a gemcitabine transporter into cells, was highlighted and might help us decide whether we benefit from gemcitabine or 5-fluorouracil in the adjuvant setting (Abstract #4006). Second, authors presented the negative predictive role of SPARC stroma and cytoplasmic expression in patients treated with adjuvant gemcitabine (within the CONCO-001 study) as they reported poor outcome of those having high expression, not seen in patients on observation (Abstract #4016). Finally, a study which might be a basis for future strategies and as great food for scientific thought suggested that selection of cytotoxic treatment based on gene expression profiling is feasible in clinical practice and may help improve treatment efficacy as well as predict for drug resistance (Abstract #4017). Of course, there is a long way to go before implementation of these genomic findings, with the exception of hENT1 which seems to be close for clinical use. Image: Transport and metabolism of gemcitabine. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->